TRIBE Uncovers the Role of Dis3 in Shaping the Dynamic Transcriptome in Malaria Parasites - Liu, Meng; Lu, Binbin; Fan, Yanting; He, Xiaohui; Shen, Shijun; Jiang, Cizhong; Zhang, Qingfeng (Frontiers in Cell and Developmental Biology, 2019)
Identification of RNA targets of RNA-binding proteins (RBPs) is essential for complete understanding of their biological functions. However, it is still a challenge to identify the biologically relevant targets of RBPs through in vitro strategies of RIP-seq, HITS-CLIP, or GoldCLIP due to the potentially high background and complicated manipulation. In malaria parasites, RIP-seq and gene disruption are the few tools available currently for identification of RBP targets. Here, we have adopted the TRIBE (Targets of RNA binding proteins identified by editing) system to in vivo identify the RNA targets of PfDis3, a key exoribonuclease subunit of RNA exosome in Plasmodium falciparum. We generated a transgenic parasite line of Pfdis3-ADARcd, which catalyzes an adenosine (A)-to-inosine (I) conversion at the potential interacting sites of PfDis3-targeting RNAs. Most of PfDis3 target genes contain one edit site. The majority of the edit sites detected by PfDis3-TRIBE locate in exons and spread across the entire coding regions. The nucleotides adjacent to the edit sites contain ~ 75% of A+T. PfDis3-TRIBE target genes are biases toward higher RIP enrichment, suggesting that PfDis3-TRIBE preferentially detects stronger PfDis3 RIP targets. Collectively, PfDis3-TRIBE is a favorable tool to identify in vivo target genes of RBP with high efficiency and reproducibility. Additionally, the PfDis3-targeting genes are involved in stage-related biological processes during the blood-stage development. Thus PfDis3 appears to shape the dynamic transcriptional transcriptome of malaria parasites through post-transcriptional degradation of a variety of unwanted transcripts from both strands in the asexual blood stage.